Bahasa Indonesia Penutur Asing Sebagai Upaya Internasionalisasi Universitas di Indonesia - Carmelia Mukti Sambas; Maya Farhanna Napitupulu; Edi Syaputra (Jurnal Multidisiplin Dehasen (MUDE), 2022)
Language is a means of communication in everyday life. The existence of Indonesian as an international language in the international arena cannot be doubted. There are several universities in Asia, Australia and mainland Europe that offer Indonesian language learning as a compulsory subject. The international formulation of language appears to require reexamination and strategy. This is for the effectiveness of the implementation of all programs that have been designed and implemented. What's even more surprising is when foreign speakers of Indonesian actually participate in the Malay language national speech program organized by the state of Malaysia. The purpose of this study is to be able to describe the importance of BIPA learning at universities and describe the implementation of the policy of independent learning in BIPA lessons at any university. The method used in this study is a qualitative descriptive method (Lina Septianasari, 2021).